Ketidaksesuaian Penggunaan Proton Pump Inhibitors (PPIs) pada Lanjut Usia dan Interaksi Obat: Kajian Naratif - Arief, Thendi Abdul; Rachmadi, Nabila Risti; Fahriah, Hanum Hasifah; Nugroho, Agung Endro (Fakultas Farmasi Universitas Mahasaraswati Denpasar, 2026)
Background: PPIs are highly effective for treating gastrointestinal disorders, including dyspepsia, peptic ulcer disease, gastritis, and gastroesophageal reflux disease (GERD). Furthermore, for the prophylaxis of NSAIDs and to mitigate gastrointestinal bleeding in patients receiving glucocorticoids, antiplatelet agents, or anticoagulants, particularly in the elderly population. The prescribing of PPIs among elderly patients remains a widespread issue that can lead to inappropriate use, hospital admission, or discharge. Additionally, the inappropriate use of PPIs can lead to possible drug-drug interactions.Objective: This narrative review aims to comprehensively assess inappropriateness associated with PPIs use in the elderly population and drug-drug interactions.Methods: Studies published from 2014 to 2024 were identified through a comprehensive search of multiple databases, including PubMed, Google Scholar, and ScienceDirect.Results: Long-term dangers such as infections and nutritional deficits are increased by inappropriate usage, which is defined by unwarranted commencement and lengthy duration. Simultaneously, PPIs present significant DDI hazards through modulating the absorption of pH-dependent medications and blocking cytochrome P450 enzymes, particularly CYP2C19. These risks are made worse by the prevalence of polypharmacy and aging-related deterioration of renal and hepatic function.Conclusion: In clinical practice, these findings call for systematic drug reviews and organized deprescribing programs to detect and manage high-risk combos. Implementing PPI stewardship programs in hospital and community settings is highly advised at the policy and systems level to enhance pharmaceutical safety in this susceptible population and to encourage evidence-based, guideline-concordant prescription.